2015
DOI: 10.1016/j.ijpsycho.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Hemifield-dependent N1 and event-related theta/delta oscillations: An unbiased comparison of surface Laplacian and common EEG reference choices

Abstract: Surface Laplacian methodology has been used to reduce the impact of volume conduction and arbitrary choice of EEG recording reference for the analysis of surface potentials. However, the empirical implications of employing these different transformations to the same EEG data remain obscure. This study directly compared the statistical effects of four commonly-used (nose, linked mastoids, average) or recommended (reference electrode standardization technique [REST]) references and their spherical spline current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 79 publications
(123 reference statements)
3
52
0
Order By: Relevance
“…However, a recent study comparing the reference schemes show that the reference used has not remarkable impact on results if brain area used in analyses corresponds the areas were the actual sources are (Kayser & Tenke, 2015b). In the case of the current research, it is assumed that primary sources of the activation to the auditory stimuli are bilaterally at the auditory cortices.…”
Section: Methodological Comparison Of Studies I-iiimentioning
confidence: 95%
See 1 more Smart Citation
“…However, a recent study comparing the reference schemes show that the reference used has not remarkable impact on results if brain area used in analyses corresponds the areas were the actual sources are (Kayser & Tenke, 2015b). In the case of the current research, it is assumed that primary sources of the activation to the auditory stimuli are bilaterally at the auditory cortices.…”
Section: Methodological Comparison Of Studies I-iiimentioning
confidence: 95%
“…In theory, the sum of all recorded EEG activity approximates zero, and because no neutral reference location exists on the human body because of volume conduction, the average reference has been preferred to all other known reference schemes when using high denseelectrode arrays (e.g., Dien, 1998;Kayser & Tenke, 2015b;Nunez & Srinivasan, 2006). The data analyzed in Study III was collected with DSAMP data acquisition software in 1990's with a limited number of channels available in the system, which made the average-referencing infeasible solution.…”
Section: Methodological Comparison Of Studies I-iiimentioning
confidence: 99%
“…Using EEGs recorded from a large sample ( N = 130) during a visual half-field paradigm, we found that CSDs revealed by far a more accurate representation of hemifield-dependent asymmetries of the posterior contralateral N1, both in time and time-frequency domains, than their surface potentials counterparts, regardless of reference scheme (average, nose, linked mastoids, reference electrode standardization technique [REST]; Kayser and Tenke, 2015). In contrast, surface potentials also revealed significant hemifield-dependent asymmetries at more anterior locations, which were presumably caused by volume conduction.…”
Section: Common Surface Laplacian Concernsmentioning
confidence: 99%
“…After reducing the signal-to-noise ratio by limiting the number of trials to compute an error-related negativity, the surface Laplacian was found to render better results than its surface potential counterparts (Cohen, 2014). We manipulated noise levels by evaluating hemifield-dependent N1 asymmetries with nonparametric permutation tests using different sample sizes ( N = 130, 80, 40, 20, or 10), which did not affect the superior performance of CSD compared to ERP or EEG measures, although overall statistical significance progressively declined with smaller sample size across all data transformations (Kayser and Tenke, 2015). …”
Section: Common Surface Laplacian Concernsmentioning
confidence: 99%
“…In our previous work, obtained for a groups of subjects rather than a single individual, CSD topographies computed with intermediate spline flexibility (m = 4) were stable and interpretable, both for ERP and resting EEG (e.g., Kayser and Tenke, 2006a, b; Tenke and Kayser, 2005; Tenke et al, 2010, 2011), as well as for event-related sychronization/desychronization (Kayser et al, 2014; Kayser and Tenke, 2015a). The present findings extend these recommendations to the study of phase properties of neuronal oscillatory activity.…”
Section: Discussionmentioning
confidence: 84%